2012
DOI: 10.1590/s1806-83242012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Does the casting mode influence microstructure, fracture and properties of different metal ceramic alloys?

Abstract: The aim of the present study was to evaluate the tensile strength, elongation, microhardness, microstructure and fracture pattern of various metal ceramic alloys cast under different casting conditions. Two Ni-Cr alloys, Co-Cr and Pd-Ag were used. The casting conditions were as follows: electromagnetic induction under argon atmosphere, vacuum, using blowtorch without atmosphere control. For each condition, 16 specimens, each measuring 25 mm long and 2.5 mm in diameter, were obtained. Ultimate tensile strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…Due to the different microhardness values of the alloys, the resultant roughness of this airborne particle abrasion may be different for each type of alloy. However, several studies have shown that some of these alloys have very close microhardness values (9,24,25) and in the present study, different bond strength values were found with the same resin cement.…”
Section: Resultscontrasting
confidence: 46%
“…Due to the different microhardness values of the alloys, the resultant roughness of this airborne particle abrasion may be different for each type of alloy. However, several studies have shown that some of these alloys have very close microhardness values (9,24,25) and in the present study, different bond strength values were found with the same resin cement.…”
Section: Resultscontrasting
confidence: 46%
“…Bauer et al13 demonstrated that when noble and basic alloys are cast in an uncontrolled environment, the metals are exposed to deleterious gases and elements, which influence their mechanical properties such as internal porosity. DMLS is a new technology in dentistry for manufacturing Co-Cr metal ceramic substructures, and therefore, the steps of the procedure and the factors that affect product quality are not well known.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the quality of a material and thus the clinical chances of success are directly affected by controlling the manufacturing environment 13-15. New manufacturing processes such as metal injection molding and powder-metallurgical techniques are being developed to achieve dental alloys with better microstructure and mechanical properties 10,16.…”
Section: Introductionmentioning
confidence: 99%
“…In the microstructure of group 2 specimens, some precipitates, which were probably constituents of chromium, molybdenum, niobioum, and silicon carbides, were also observed in the dendritic region . The microstructure in this group also started to reveal the grain boundaries partially.…”
Section: Discussionmentioning
confidence: 86%
“…High‐temperature heat treatments and repeated PFM firing cycles have been shown to affect alloy microstructures, surface oxides, corrosion, and physical and mechanical properties. To date, few studies have evaluated the effects of high temperature attained during PFM firing on the mechanical properties and microstructure of Ni‐Cr alloy . However, no study has been carried out to evaluate the changes in mechanical properties, microstructure, and X‐ray diffraction (XRD) pattern of the alloy after each firing.…”
mentioning
confidence: 99%